MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMK NEGERI 1 PELEPAT ILIR PADA POKOK BAHASAN MEMBUAT KESEPAKATAN MELALUI NEGOSIASI DENGAN MODEL PENDEKATAN DISCOVERY LEARNING TAHUN PELAJARAN 2017/2018 - Wasito Wasito (PAKAR Pendidikan, 2018)
Learning outcomes of students of class X marketing SMK Negreri 1 Pelepat Ilir on the subject Making Agreement Through Negotiation of basic competence 3.10 Evaluating the submission, quote and agreement in oral and written negotiation text in Lesson Year 2017/2018 after analyzed has low result, this is allegedly because the approach learning at that time is not right, then in this class research used approach learning Discovery Learning which emphasize concept learn discovery of data, process data hinga make conclusion. The issues that will be discussed are whether the Indonesian language learning subject makes agreement through negotiation of basic competence 3.10 Evaluating the submission, quote and agreement in oral and written negotiation text with discovery learning approach can increase? While the purpose of this research to find out the improvement of student learning outcomes with the model of discovery learning approach. The location of this research was conducted at SMK Negeri 1 Pelepat Ilir, Pelepat Ilir District, Bungo District, Jambi. The type of research to be carried out in this study is classroom action research. The result of learning discovery learning method can improve student learning outcomes.